Sustainable Energy in Island States: Comparative Analysis of New Trends in Energy Digitalization and the Experience of the UK, Japan, Indonesia and Cyprus - Loseva, Olga V.; Karpova, Svetlana V.; Rasteryaev, Konstantin O.; Sokolova, Elizaveta S.; Makar, Svetlana V.; Kharchilava, Khvicha P. (International Journal of Energy Economics and Policy, 2020)
Island states such as the ones discussed in this article are dependent on energy imports, which puts a lot of pressure on their budgets. In addition, limited land areas and difficult environmental conditions contribute to the need to transform the energy sector. Such a transformation in modern conditions is possible only in the direction of sustainable energy. This transition is complex and requires several parallel processes, one of which is the digitalization of the energy sector. The countries studied in this article started the process of transforming their energy sectors, and the results are different. The article is aimed at disclosing the current state and prospects in the energy sector in the context of developing a universal strategy for sustainable energy transformation. The authors point out the main achievements and barriers in this area and develop a multiplier to find out the real situation in the sector in island states. The key findings of the article include the development of a multiplier, evidence that institutional barriers are central to sustainable energy development, and a comprehensive analysis of the role of digitalization in shaping a sustainable energy system. Keywords: Sustainable energy, digitalization, institutions, energy costs, Island States JEL Classifications: O13; Q42 DOI: https://doi.org/10.32479/ijeep.10571